Deep sequencing of GDF5 reveals the absence of rare variants at this important osteoarthritis susceptibility locus. - Dodd, A; Rodriguez-Fontenla, C; Calaza, M; Carr, A; Gomez-Reino, J; Tsezou, A; Reynard, L; Gonzalez, A; Loughlin, J (2011)
OBJECTIVE: The common single nucleotide polymorphism (SNP) rs143383 in the 5' untranslated region (5'UTR) of growth and differentiation factor 5 (GDF5) is strongly associated with osteoarthritis (OA) and influences GDF5 allelic expression in vitro and in the joint tissues of OA patients. This effect is modulated in cis by another common SNP, also located within the 5'UTR, whilst a common SNP in the 3'UTR influences allelic expression independent of rs143383. DNA variants can be common, rare or extremely rare/unique. To therefore enhance our understanding of the allelic architecture of this very important OA susceptibility locus we sequenced the gene for potentially functional and novel rare variants. METHOD: Using the Sanger method we sequenced GDF5 in 992 OA patients and 944 controls, with DNA changes identified by sequencing software. We encompassed the protein-coding region of the two GDF5 exons, both untranslated regions and approximately 100 bp of the proximal promoter of the gene. RESULTS: We detected 13 variants. Six were extremely rare with minor allele frequencies (MAFs) of ≤ 0.0006. One is in a predicted transcription factor binding site in the GDF5 promoter whilst two substitute conserved amino acids. The remaining seven variants were common and are previously known variants, with MAFs ranging from 0.025 to 0.39. There was a complete absence of variants with frequencies in-between the extremely rare (n=6) and the common (n=7). CONCLUSIONS: This is the first report of the deep sequencing of an OA susceptibility locus. The absence of rare variants informs us that within the regions of the gene that we have sequenced GDF5 does not harbour any novel variants that are able to contribute, at a population level, to the OA association signal mediated by rs143383 nor does it harbour, at a population level, any novel variants that can influence OA susceptibility independent of rs143383.